DOMINO, doxycycline 40 mg vs. minocycline 100 mg in the treatment of rosacea: a randomized, single‐blinded, noninferiority trial, comparing efficacy and safety. (1st June 2017) - van der Linden, M.M.D.; van Ratingen, A.R.; van Rappard, D.C.; Nieuwenburg, S.A.; Spuls, Ph.I.
Summary: Background: There is a lack of evidence for minocycline in the treatment of rosacea. Objectives: To compare the efficacy and safety of doxycycline 40 mg vs. minocycline 100 mg in papulopustular rosacea. Methods: In this randomized, single‐centre, 1 : 1 allocation, assessor‐blinded, noninferiority trial, patients with mild‐to‐severe papulopustular rosacea were randomly allocated to either oral doxycycline 40 mg or minocycline 100 mg for a 16‐week period with 12 weeks of follow‐up. Our primary outcomes were the change in lesion count and change in patient's health‐related quality of life (using RosaQoL). Intention‐to‐treat and per protocol analyses were performed. Results: Of the 80 patients randomized (40 minocycline, 40 doxycycline), 71 were treated for 16 weeks. Sixty‐eight patients completed the study. At week 16, the median change in lesion count was comparable in both groups: doxycycline vs. minocycline, respectively 13 vs. 14 fewer lesions. The RosaQoL scores were decreased for both doxycycline and minocycline, respectively by 0·62 and 0·86. Secondary outcomes were comparable except for Investigator's Global Assessment success, which was seen significantly more often in the minocycline group than in the doxycycline group (60% vs. 18%, P < 0·001). At week 28, outcomes were comparable, except for RosaQoL scores and PaGA, which were significantly different in favour of minocycline ( P = 0·005 and P = 0·043, respectively), and fewer relapses were recorded in the minocycline group than in the doxycycline group (7% and 48%, respectively; P < 0·001). No serious adverse reactions were reported. Conclusions: Minocycline 100 mg is noninferior to doxycycline 40 mg in efficacy over a 16‐ week treatment period. At follow‐up, RosaQoL and PaGA were statistically significantly more improved in the minocycline group than in the doxycycline group, and minocycline 100 mg gives longer remission. In this study there was no significant difference in safety between these treatments; however, based on previous literature minocycline has a lower risk‐to‐benefit ratio than doxycycline. Minocycline 100 mg may be a good alternative treatment for those patients who, for any reason, are unable or unwilling to take doxycycline 40 mg.